Design of simple and compact tunable fibre laser. Issue 12 (1st June 2015) - Fujimoto, Y.; Ishii, O.; Yamazaki, M.
Abstract : A novel design of a simple and compact tunable fibre laser that uses the chromatic aberration of the lens relay and a slit‐like effect of the optical fibre core is proposed and demonstrated. The tunability of 20 nm is obtained by 130 µm of cavity output mirror adjustment.